2001
DOI: 10.1303/aez.2001.77
|View full text |Cite
|
Sign up to set email alerts
|

Chemical ecology of astigmatid mites. LVIII. 2-Hydroxy-6-methylbenzaldehyde: Female sex pheromone of Cosmoglyphus hughesi Samsinak(Acari: Acaridae).

Abstract: 2-Hydroxy-6-methylbenzaldehyde (2,6-HMB) was identified as the female sex pheromone from the acarid mite, Cosmoglyphus hughesi. Although the sex pheromone functioned to stimulate males to tap females and then mount, it was detectable as a major component of hexane extracts not only from females but also from males and protonymphs. Its contents were estimated to be 283.1Ϯ49.4 ng per female, 135.2Ϯ25.5 ng per male and 3.8Ϯ0.4 ng per protonymph. Sexual activity was induced in males by exposure of a filter paper i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 16 publications
2
10
0
Order By: Relevance
“…Other than S-isorobinal, the following compounds have been identified as sex pheromones from nine species other than the present study; 2-hydroxy-6-methylbenzaldehyde (HMB) in Acarus immobilis Griffiths (Sato et al 1993), in Cosmoglyphus hughesi Samsˇinˇa´k (Ryono et al 2001), in Aleuroglyphus ovatus Troupeau (Kuwahara et al 1992a) and in Dermatophagoides farinae Hughes (Tatami et al 2001), undecane in C. rodriguezi Samsˇinˇa´k (Mori et al 1995), (2R,3R)-epoxyneral in Caloglyphus sp. MJ (Mori et al 1996), rosefuran in Caloglyphus sp.…”
Section: Discussionmentioning
confidence: 59%
“…Other than S-isorobinal, the following compounds have been identified as sex pheromones from nine species other than the present study; 2-hydroxy-6-methylbenzaldehyde (HMB) in Acarus immobilis Griffiths (Sato et al 1993), in Cosmoglyphus hughesi Samsˇinˇa´k (Ryono et al 2001), in Aleuroglyphus ovatus Troupeau (Kuwahara et al 1992a) and in Dermatophagoides farinae Hughes (Tatami et al 2001), undecane in C. rodriguezi Samsˇinˇa´k (Mori et al 1995), (2R,3R)-epoxyneral in Caloglyphus sp. MJ (Mori et al 1996), rosefuran in Caloglyphus sp.…”
Section: Discussionmentioning
confidence: 59%
“…Neral also serves as a sex pheromone in some other Astigmata (Hiraoka et al 2002). The aromatic compound 2,6-HMBD-in C. gigantea showing strong alarm pheromonal activity-possesses either alarm pheromonal or sex pheromonal properties in certain astigmatid mite species (Leal et al 1988;Kuwahara et al 1992;Sato et al 1993;Ryono et al 2001). Since these ''astigmatid compounds'' are widespread in Oribatida, we should expect to frequently find semiochemical roles of oil glands in the latter group as well.…”
Section: Chemoreceptionmentioning
confidence: 99%
“…1) The alarm pheromones have been identied in 16 species, the aggregation pheromones in two species, and the sex pheromones in seven species. 1,2) Several compounds also function as anti fungal substances. [3][4][5] In the present study, two monoterpenoids were newly found from the acarid mite Schwiebea araujoae, and from an unidentiˆed Rhizoglyphus sp.…”
Section: -(4-methylmentioning
confidence: 99%